THE DETERMINATION OF MARINE TRAINING WITH FUZZY MULTI CRITERIA DECISION MAKING APPROACH - Wisono Setiawan; Okol S Suharyo (JOURNAL ASRO, 2018)
ABSTRACT Navy as a marine security defense force has an Integrated Armored Weapon System (SSAT), one of them is the power of Submarine and the amount of it will continue to evolve. The current condition demands to perform development and review of strategic and optimal submarine training areas to support the exercise and preparedness of the submarine's strength to prepare the readiness of combat conditions. The purpose of this study was to determine the best criteria for the location of the submarine training by analyzing and reviewing some of the existing locations of Navy Submarine Exercise practice and doing further development. In the selection of submarine training criteria, the method used was the Fuzzy Multiple Decision-Making Criteria (FMCDM). Keywords: Determination Criteria, Training Location, Fuzzy MCDM